Métodos para ensino de óptica para alunos portadores de deficiência visual - Oliveira, Antônia Cristina Campos Paz (2018)
"Methods for the teaching of optics for students with visual impairment", is a project that seeks to assist teachers in introducing introductory concepts to the teaching of vision, ranging from the anatomy of the eye, as well as its main functions to the through the crossing of the light beams. For this introduction, it is necessary to construct play experiments and adapted to low-cost students, but due to the large number of students included and low qualification in teacher training, this project proposes a social inclusion, and can be applied very easily in the classroom with all students included. Its development was based on the conceptual field theory of gerard vergnaud, who was a disciple of jean piaget and a great admirer of vygotsky's theories, and proposed a cognitive teaching-learning method in the area of complex competences related to science teaching, its main objective is to allow, through a framework, the understanding of the affiliations and ruptures between knowledge, in children and adolescents. The application took place at the state school joana rodrigues vieira, located at lourival munis street, 514, glória neighborhood, in the 4th year of elementary school i, with low vision students with visual remnants of 9 and 10 years of age . the project was instrumental in increasing students' knowledge about optics teaching, students performed a pre-test to identify the level of knowledge about the content addressed, the pre-test followed the format of questions and answers, where the teacher asked and the students answered in the braille machine, after this procedure the experiment was carried out and then the post-test, which had fundamental importance to filter the student's level of learning, showing their cognitive development and the role of the student as protagonist in the teaching - learning process.